Perceived Flirting Skills Mediate the Relationship between Sociosexuality and Singlehood Status Among Young Adults in Colombia. - Mendoza, Juan; Romero, Duban; Mebarak, Moisés; Rodrigues, David L.; Martinez, Martha (Sexuality & Culture, 2025)
Past research has linked sociosexuality and flirting skills to different types of singlehood. Individuals with unrestricted sociosexuality are less likely to enter long-term relationships or experience involuntary singlehood, whereas shyness and low self-confidence are common reasons for involuntary singlehood. However, existing studies tend to focus solely on direct associations between sociosexuality, courtship behaviors, and singlehood status, overlooking potential interaction effects among these factors. In this cross-sectional study of 816 Colombian young adults (487 women and 329 men), we examined whether flirting self-efficacy beliefs mediate the relationship between sociosexuality and singlehood status. Multinomial logistic regression models indicated that higher levels of unrestricted sociosexuality and greater perceived flirting self-efficacy were associated with a decreased likelihood of reporting singlehood due to difficulty finding a partner. Moreover, structural equation models demonstrated that flirting self-efficacy mediates the relationship between sociosexuality and singlehood status. These findings underscore the importance of flirting self-efficacy in the mating process and illuminate pathways through which sociosexuality influences singlehood status in the Latin American context.